Development and pilot testing of the "focus on the person" form: Supporting care transitions for people with dementia. (August 2019) - Burton, Elissa; Slatyer, Susan; Bronson, Mary; Nichols, Pam; Quested, Eleanor; Hill, Andrew; Maher, Sean; Aoun, Samar; Hill, Keith D; Kuno, Yukiko; Toye, Chris
When people with dementia are hospitalised, their capacity to communicate with the staff may be limited, compounding risks of distress and other adverse outcomes. Opportunities for carers to share relevant information to inform appropriate person-centred care are also limited. This four-phase mixed methods study aimed to develop an evidence-based family carer–staff communication form, the Focus on the Person form, to address this concern. In Phase I, a literature review plus consultation with clinicians and carers informed form development. In Phase II, the professionally formatted form was piloted by 31 family carers, who were then interviewed about their experiences. These data, combined with data from 30 hospital staff members who participated in Phase III focus groups, led to final, Phase IV, refinements of the form. The form now provides an opportunity for families to inform the person-centred care of people with dementia in hospital, potentially improving outcomes for this vulnerable group.